Screening for Cervical Cancer – Minimise Risks – Maximise Benefits. Need for Adaptation in Germany in Light of the European Guidelines and Their Objectives - Simoes, E.; Brucker, S.; Beckmann, M. W.; Ortmann, O.; Albring, C.; Wallwiener, D. (Geburtshilfe und Frauenheilkunde, 2013)
The national cancer plan calls for adjustment of the early detection scheme for cervical cancer to the quality requirements of the “European guidelines for quality assurance in cervical cancer screening”. The existing scheme should be further developed and carried out in an organized, population-based framework. The objective is to lower the incidence and mortality of cervical cancer while minimising the risks and optimising the benefits of the scheme. The self-determined choice of the patients should be respected. The competence for this task falls in the medical field of activity. The adaptation includes an organisational further development and, in part, re-organisation of the established early detection scheme for cervical cancer. If the national cancer plan is considered as a concept for the discursive further development of the healthcare, the experts from different areas of the system are encouraged to participate. To go to a new version of the national directive for early detection of cancer that will define the procedure in the Federal Republic in future first requires a consensus of the fields of action with regard to the specified objectives of the transformation. The heterogeneity of the approaches in Europe (even within individual countries) as well as the results clearly show that Germany has to find and define its own pathway. The presented overview of the pending fields of action could serve as a basis for the development process and the work of a multisectoral task force in the field of gynaecology.
Keywords: cervical cancer; cervix; precancerous cervix; cancer register; gynaecology